Existence of Fixed Point Results in G-Metric Spaces. (16th July 2009) - Mustafa, Zead; Shatanawi, Wasfi; Bataineh, Malik
Abstract : The purpose of this paper is to prove the existence of fixed points of contractive mapping defined on G -metric space where the completeness is replaced with weaker conditions. Moreover, we showed that these conditions do not guarantee the completeness of G -metric spaces.